Aural exploration of post-tonal music theory: an automatic musical variations generator in MAX - Allen Alonso Torres-Matarrita (2018)
Some tendencies in post-tonal music are regarded as very "cerebral" or "cryptic", and usually are misunderstood when not rejected by the general public and some professional musicians. As an effort to overcome resistance to this languages, I designed an interactive application in MAX that allow to improvise using Allen Forte's set theory. So, rather than being forced to do a bunch of arithmetic calculations by heart before play a single note, musicians can hear instantly the aural qualities of determined pitch class sets by playing a simple chord in a MIDI keyboard to generate variations of a previously played musical gesture. An iterative design process was carried on, and the results, conclusions and reflections during the different stages of the work showed the relevance of the music theory applied and its relation to constraint satisfaction techniques in music composing processes.